2007
DOI: 10.1542/peds.2006-1757
|View full text |Cite
|
Sign up to set email alerts
|

Adverse Associations of Sleep Problems in Australian Preschoolers: National Population Study

Abstract: Given that sleep problems are very common, the adverse outcomes shown here could affect the transition to school for a very large number of preschoolers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
151
1
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 217 publications
(168 citation statements)
references
References 26 publications
15
151
1
1
Order By: Relevance
“…9,17,18 Night waking frequency was reported in the United States as 35%, in Switzerland as 30.8%, and in Australia as 17.8%. [19][20][21] In our study, night waking was more common than reported in the literature. Night waking is the best predictor of "severe sleep problem" during childhood.…”
Section: Discussionsupporting
confidence: 51%
“…9,17,18 Night waking frequency was reported in the United States as 35%, in Switzerland as 30.8%, and in Australia as 17.8%. [19][20][21] In our study, night waking was more common than reported in the literature. Night waking is the best predictor of "severe sleep problem" during childhood.…”
Section: Discussionsupporting
confidence: 51%
“…[2][3][4][5][6][7] In this age group, the majority of sleep problems are behavioral in nature. For example, in a population sample of 4000 Australian children aged 6 to 7 years, sleep problems such as bedtime resistance and night waking occurred in 16% to 21% of children and were associated with poorer child behavior, health-related quality of life, and learning.…”
mentioning
confidence: 99%
“…One, a large nationally representative cross-sectional sample of 5000 Australian 4-to 5-year-olds, found that neither SDQ total, nor the Hyperactivity, Peer, or Emotional scale (actual) scores were greater among children with "snoring and/or breathing difficulties" during sleep $4 times per week. 33 Likewise, among 635 6-to 8-year-olds, snoring $1 time per week in the past 6 months was not associated with high (upper 10th percentile) SDQ scores. 34 This is the first study to assess SDB as a trajectory of combined symptoms, across a key period of SDB development from 6 months to 81 months, in a large sample.…”
Section: Discussionmentioning
confidence: 85%
“…33,34 Based on this literature review, and exploratory analyses, 15 potential confounders were incorporated into analyses.…”
Section: Behavior Assessmentmentioning
confidence: 99%